2020
DOI: 10.1007/s42399-020-00569-6
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Injury Is Associated with Higher Morbidity and Mortality in Patients with 2019 Novel Coronavirus Disease (COVID-19)

Abstract: COVID-19 pandemic, a global health disaster, has resulted in substantial morbidity and mortality across the globe since emerging on December 2019. Studies have shown that cardiovascular manifestations and complications linked to COVID-19 can be attributed to unfavorable clinical outcome and poor prognosis. Adult patients with laboratory-confirmed COVID-19 requiring hospitalization in participating centers between March and June 2020 were included. Data including demographics, laboratory findings, comorbidities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…The estimated 30-day survival probability for a profile patient with pre-existing CHD (65-year-old woman with no other comorbidities) was 0.5 (95% CI 0.3-0.8). Furthermore, a study in Oman [27] found that patients with cardiac injury had higher mortality than those without cardiac injury (53.3% vs 7.1%). The literature review by de Almeida-Pittito [13] mentioned above also suggested that cardiovascular disease was strongly associated with both severity and mortality, respectively (OR 4.0 95% CI 2.8-5.9 and OR 6.3 95% CI 3.7-10.8) also reflecting the previous findings [10].…”
Section: Covid-19 and Hypertension/cardiovascular Diseasesmentioning
confidence: 99%
“…The estimated 30-day survival probability for a profile patient with pre-existing CHD (65-year-old woman with no other comorbidities) was 0.5 (95% CI 0.3-0.8). Furthermore, a study in Oman [27] found that patients with cardiac injury had higher mortality than those without cardiac injury (53.3% vs 7.1%). The literature review by de Almeida-Pittito [13] mentioned above also suggested that cardiovascular disease was strongly associated with both severity and mortality, respectively (OR 4.0 95% CI 2.8-5.9 and OR 6.3 95% CI 3.7-10.8) also reflecting the previous findings [10].…”
Section: Covid-19 and Hypertension/cardiovascular Diseasesmentioning
confidence: 99%
“…Among these articles, 7 articles overlapped study data with other articles, and 185 articles met the other exclusion criteria. Finally, 56 articles remained [ [2] , [3] , [4] , 9 , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Another study reported 21.7% cardiac injury incidence and identified age, hypertension, chronic heart failure, diabetes, chronic obstructive pulmonary disease/asthma as risk factors for cardiac injury in COVID-19. Outcomes for patients with cardiovascular injuries were worse including increased incidence of mechanical ventilation, acute respiratory distress syndrome, acute kidney injury, anemia and death 20 . An international, multicenter cohort study including 7 hospitals consisting of 305 hospitalized COVID-19 patients in New York City and Milan found myocardial injury was observed in 62.3% of patients.…”
Section: Discussionmentioning
confidence: 99%